Willingness to pay for turtle conservation and the financial viability of Rantau Abang turtle sanctuary, Terengganu - Samdin, Zaiton (2002)
Conservation is an important measure to ensure that the endangered turtles will be able to survive for the benefit of future generations. Cardinal approach i.e. Contingent Valuation Method was used in this study to evaluate the willingness to pay for conservation of turtles in Rantau Abang, Terengganu. The study also estimated the benefits of turtle conservation, evaluated the viability of the existing Turtle Sanctuary and identified the factors that influenced society's willingness to pay for turtle conservation based on a survey of different groups of respondents. Three different groups of respondents i.e. group A (residents), group B (visitors to Rantau Abang Turtle Sanctuary) and group C (tourists) were classified in this study. Each group consists of a different number of sample sizes i.e. 110 for group A, 100 and 130 for groups B and C respectively. In the estimation of benefits for each group of respondents, the Contingent Valuation Method yielded mean values of RM10.02, RM107.11 and RM61.93 using the Logit technique. It is also found that among the factors that influenced willingness to pay for turtle conservation for groups A and B were bid, monthly income and age. For group C, bid, monthly income and membership in some environmental organisations were the main factors influencing peoples' willingness to pay. The study also evaluated the role of government contribution to the viability of the project. Using RM10 as the ticket price and with the government allocation of RM150,000, the financial analysis showed that the Net Present Value (NPV) was RM1,27,603.45. However, without government allocation, the NPV was negative RM6,229.77. This infers that the government contribution is essential to ensure the viability of the project. In fact, with the current contribution of RM150,000, the ticket price could be reduced to RM5 and the project would still be viable. At this ticket price, the NPV was RM263,649.15. A sensitivity analysis showed that the project was still viable even with a 10% decrease in total cash inflow or with a 10% increase in total cash outflow. Further analysis was carried out to determine the amount of government allocation needed for the project to reach break-even point only. At the ticket price of RM10, the amount of government allocation that made the NPV equaled zero was RM700.59 per year. At the price of RM5, the amou nt of government allocation was RM120,350.59 per year.